COMPETENCY DEVELOPMENT OF APPARATUS THROUGH EDUCATION AND TRAINING AT THE PERSONNEL AND HUMAN RESOURCE DEVELOPMENT AGENCY OF BADUNG REGENCY, BALI PROVINCE - Ekowati, Maria; Nopianti, I Putu (Media Inovasi Pendidikan dan Publikasi, 2024)
Apparatus resources are one of the most important factors in a government institution in addition to other factors such as money, technology-based tools such as computers, the internet. Therefore, natural resources management should be carried out in a professional way so that a balance between the capabilities of natural resources and organizational needs can be realized so that they can develop productively. In Government Regulation No. 11/2017 concerning Civil Servant Management, which contains competency development, which is followed by Circular Letter No. 28/2021 which regulates Competency Development for Civil Servants through the Education route. BKPSDM Badung Regency, Bali Province plays a very important role in improving the performance of quality employees through training programs. In the implementation of the management of BKPSDM civil servants, they encounter obstacles, both internal and external obstacles. The purpose of the research is to analyze how the Development of Apparatus Resource Competency through Training at BKPSDM Badung Regency, Bali Province. Methods: This research is a qualitative method. The results of the research show that the development of Civil Servant competencies organized by the Badung Regency BKPSDM has been carried out well but is not optimal. There are several factors that hinder the development of civil servant competencies through training, including facilities and infrastructure, lack of budget allocation for training programs, lack of employee motivation. So it can be concluded that the Badung Regency BKPSDM has been quite helpful in terms of making the wrong implementation of training effective, although it can still be said that it is not optimal.